Pola Pertumbuhan Pseudomonas sp. dengan Menggunakan Variasi Konsentrasi D-glukosa dalam Media Pertumbuhan terhadap Waktu Inkubasi - Agusniar Furkani Listyawati (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2016)
This study was to determine the growth pattern of Pseudomonas sp. by administering various concentration of D-glucose to the growth medium and to see its effect on various incubation times. Addition of D-Glucose in the growth medium as a source of bacterial carbon that can support the cell growth process. The results showed that, the use of D-glucose with various concentration in growth media of Pseudomonas sp. affect the formation of bacterial cell growth patterns. This study showed that Pseudomonas sp. using D-glucose substrate for it’s cell growth. While the longer incubation time didn’t had effect for the cell growth pattern due to the ability of bacteria in consuming substrates that are added to the growth medium.